What Privacy and Confidentiality Mechanisms are used in the Electronic Health Records (Clinical Master and ICT4 M-Power systems)? A design Science Research Approach. - Orishaba , Glorious; Serunjogi, David (Student’s Journal of Health Research Africa, 2022)
Background: Patients are required to share information with their doctors to facilitate correct diagnosis and determination of treatment, especially to avoid adverse drug interactions. Despite efforts to fully implement and adopt Electronic Health Records System, there is limited attention to fully secure patients’ details. Issues of privacy and confidentiality still remain a major concern at health facilities mainly in developing countries like Uganda. This study aimed to determine what privacy and confidentiality mechanisms are used in the EHRs (Clinical Master and ICT4 M-Power systems Methods: The study used a design science research approach that adopted qualitative methods. Data Flow Diagrams were used to design the desired artifact while the development of the encryption and decryption tool, we used the Hypertext Pre-Processor(PHP) time platform, which is an object-oriented programming language and is a block component that is made up of Cascade Style Sheet (CSS) and HTML(hypertext markup language ) embedded in PHP for it to be fully functional and be able to connect to and run on the server where most of the records and details of the activities are stored in the database. Results: The respondents pointed at various current mechanisms for privacy and confidentiality that included; user credentials, segregation of roles, Physical access control, international access policies, interlocked interface screens, and training of users. Conclusion: The inclusion of encryption and decryption features are very vital to enhancing health facilities’ capacity and measures for establishing the privacy and confidentiality of patients’ data. Recommendation: The Ministry of Health, Uganda, and implementers of EHR should adopt the encryption and decryption tool for use at the health facilities as the second layer of security to ensure the privacy and confidentiality of patients’ data.